Diglycosidic indole alkaloid derivatives from an aqueous extract of Isatis indigotica roots. Issue 6 (3rd June 2017) - Meng, Ling-Jie; Guo, Qing-Lan; Xu, Cheng-Bo; Zhu, Cheng-Gen; Liu, Yu-Feng; Chen, Ming-Hua; Lin, Sheng; Li, Yu-Huan; Jiang, Jian-Dong; Shi, Jian-Gong
Abstract: Six new indole alkaloid diglycosides named isatigotindolediosides A-F (1–6 ), along with three known analogs (7–9 ), were isolated from an aqueous extract of the Isatis indigotica roots (ban lan gen). Their structures including the absolute configurations were determined by comprehensive spectroscopic data analysis, combined with enzyme or acid hydrolysis, and comparison of experimental circular dichroism (CD) and calculated electronic circular dichroism (ECD) spectra. In the preliminary assays, compounds3, 5, and8 showed antiviral activity against Coxsackie virus B3. Abstract :